Fear your strengths : what you are best at could be your biggest problem - Kaplan, Robert E. (BK business book., 2013)
Once you've discovered your strengths, you need to discover something else: your strengths can work against you. -- Fear Your Strengths provides tools to help you become aware of your leadership leanings and excesses and provides insights for combating the mindset that encourages them. It offers a practical psychology of leadership, a better way for leaders to calibrate their performance so that you can make sure your strengths don't overpower you but rather move you--and your organization--forward.